Insights from the complete chloroplast genome into the evolution of Sesamum indicum L. - Haiyang Zhang (Public Library of Science (PLoS), 2013)
Sesame (Sesamum indicum L.) is one of the oldest oilseed crops. In order to investigate the evolutionary characters according to the Sesame Genome Project, apart from sequencing its nuclear genome, we sequenced the complete chloroplast genome of S. indicum cv. Yuzhi 11 (white seeded) using Illumina and 454 sequencing. Comparisons of chloroplast genomes between S. indicum and the 18 other higher plants were then analyzed. The chloroplast genome of cv. Yuzhi 11 contains 153,338 bp and a total of 114 unique genes (KC569603). The number of chloroplast genes in sesame is the same as that in Nicotiana tabacum, Vitis vinifera and Platanus occidentalis. The variation in the length of the large single-copy (LSC) regions and inverted repeats (IR) in sesame compared to 18 other higher plant species was the main contributor to size variation in the cp genome in these species. The 77 functional chloroplast genes, except for ycf1 and ycf2, were highly conserved. The deletion of the cp ycf1 gene sequence in cp genomes may be due either to its transfer to the nuclear genome, as has occurred in sesame, or direct deletion, as has occurred in Panax ginseng and Cucumis sativus. The sesame ycf2 gene is only 5,721 bp in length and has lost about 1,179 bp. Nucleotides 1-585 of ycf2 when queried in BLAST had hits in the sesame draft genome. Five repeats (R10, R12, R13, R14 and R17) were unique to the sesame chloroplast genome. We also found that IR contraction/expansion in the cp genome alters its rate of evolution. Chloroplast genes and repeats display the signature of convergent evolution in sesame and other species. These findings provide a foundation for further investigation of cp genome evolution in Sesamum and other higher plants.